High-strength plastic corrosion-resistant microalloyed low-cost magnesium alloy and preparation method thereof
A micro-alloyed magnesium alloy with controlled composition and process parameters achieves enhanced strength, plasticity, and corrosion resistance, addressing the limitations of existing magnesium alloys in cost and efficiency.
Patent Information
- Application Number
- CN202411369757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Existing magnesium alloys face challenges in simultaneously improving strength, plasticity, and corrosion resistance while minimizing alloy additions, rare earth content, and production costs.
A high-strength, plastic, corrosion-resistant magnesium alloy composed of specific components (manganese, zinc, cerium, and aluminum) is prepared through a controlled melting, homogenization, quenching, and extrusion process, using a mixed gas atmosphere and optimized parameters to achieve a yield strength of ≥275 MPa and elongation of ≥17.5%, with a corrosion rate of ≤0.3 mm/year in a 3.5% NaCl solution.
The alloy achieves superior mechanical properties and corrosion resistance with reduced alloy and rare earth content, simplified processes, and lower production costs, suitable for industrial production.
Smart Images

Figure CN119242998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to a high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy and a preparation method thereof. Background Art
[0002] As the lightest metal structural material, magnesium alloy has the advantages of low density, high specific strength and specific stiffness, good damping and machinability, and easy recycling. It is known as the "green material of the 21st century". Magnesium and its alloys have received great attention as lightweight structural metal materials, especially in the potential applications in aerospace, transportation 3C products, medicine and chemical industries. It is difficult to simultaneously improve the strength and plasticity of existing magnesium alloys or any combination of strength and corrosion resistance or plasticity and corrosion resistance. To improve the strength and plasticity of magnesium alloys, it is necessary to add a large amount of alloying elements or rare earths, or complex processes, but the addition of high-content alloys or high-content rare earths will cause poor processing formability of magnesium alloys, low yield, high manufacturing costs, and is not conducive to the large-scale production of magnesium alloys. Therefore, how to reduce the amount of alloy addition, rare earth content, reduce costs and simplify the process, and simultaneously improve the strength, plasticity and corrosion resistance of the alloy is a technical problem that needs to be solved urgently. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy. The high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy is composed of the following components by mass percentage: manganese: 0.1-0.6%, zinc: 0.2-0.4%, cerium: 0.05-0.2% and aluminum ≤0.2%, alloy addition ≤1.4%, unavoidable impurities ≤0.05%, and the balance is magnesium. Its preparation method comprises the following steps:
[0004] (1) According to the proportion of alloy components, under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride, the volume ratio of carbon dioxide to sulfur hexafluoride is 90-99:1-10, pure magnesium is kept at 300-350° C. for 60-120 min, and then the temperature is raised to 690-710° C. to melt the pure magnesium to obtain a magnesium melt, pure zinc, pure aluminum, magnesium-manganese, and magnesium-cerium master alloys are selected as alloy materials, the alloy materials are preheated at 200-250° C. for 60-90 min, and then added to the magnesium melt in sequence, and then the temperature is raised to 700-720° C. to melt the master alloy, and then stirred evenly and kept warm for 10-20 min, and then argon gas is blown into it for refining and slag removal to obtain a magnesium alloy melt, and then poured into a mold at 200-300° C. by gravity casting to obtain an alloy ingot;
[0005] (2) homogenizing and quenching the alloy ingot obtained in step (1), then extruding after keeping it at 300-350° C. for 60-120 min, and then air-cooling it to room temperature to obtain a high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy, wherein the homogenizing treatment is carried out at 460-500° C. for 22-26 h, the quenching is carried out at room temperature and water-cooled to room temperature; the extrusion has an extrusion ratio of 25-28:1 and an extrusion speed of 0.1-0.3 mm / s;
[0006] The high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy obtained in step (2) has a yield strength of ≥275 MPa and an elongation of ≥17.5%; after being immersed in a 3.5% NaCl solution for 15 days, the corrosion rate of the alloy is ≤0.3 mm / year;
[0007] Furthermore, in terms of mass percentage, the manganese is 0.2-0.5wt.%, the zinc is 0.25-0.35wt.%, the cerium is 0.1-0.15wt.%, and the aluminum is 0≤≤0.15%.
[0008] Furthermore, the magnesium alloy obtained in step (2) has a yield strength of 280-320 MPa and an elongation of 25-30%. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is a room temperature mechanical property curve of the Mg-0.6Mn-0.4Zn-0.2Ce alloy of Example 1; DETAILED DESCRIPTION
[0010] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0011] Example 1
[0012] Taking Mg-0.6Mn-0.4Zn-0.2Ce alloy as an example (based on mass percentage, it is composed of the following components: manganese: 0.6%, zinc: 0.4%, cerium: 0.2%, unavoidable impurities ≤ 0.05%, and the balance is magnesium), its preparation method includes the following steps:
[0013] (1) According to the alloy component ratio, pure magnesium is kept at 340° C. for 60 minutes under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide to sulfur hexafluoride is 99:1), and then the temperature is raised to 690° C. to melt the pure magnesium to obtain a magnesium melt, and pure zinc, magnesium-manganese, and magnesium-cerium master alloys are selected as alloy materials. After the alloy materials are preheated at 200° C. for 90 minutes, they are added to the magnesium melt in sequence, and then the temperature is raised to 700° C. to melt the master alloy, and then the mixture is stirred evenly and kept warm for 10 minutes, and then argon gas is blown into the mixture for refining and slag removal to obtain a magnesium alloy melt, and then the mixture is poured into a mold at 200° C. by gravity casting to obtain an alloy ingot;
[0014] (2) The alloy ingot obtained in step (1) is homogenized and then immediately quenched, wherein the homogenization treatment is performed by keeping the alloy ingot at 480° C. for 24 hours, and the quenching is performed by water cooling at room temperature to room temperature; then keeping the alloy ingot at 300° C. for 60 minutes, and then extruding the alloy at 300° C. with an extrusion ratio of 28:1 and an extrusion speed of 0.1 mm / s, and then air cooling the alloy to room temperature to obtain a Mg-0.6Mn-0.4Zn-0.2Ce alloy.
[0015] The Mg-0.6Mn-0.4Zn-0.2Ce alloy obtained in step (2) has a yield strength of 320 MPa and an elongation of 17.5%. After the alloy is immersed in a 3.5% NaCl solution for 15 days, its corrosion rate is 0.26 mm / Year.
[0016] Example 2
[0017] Taking Mg-0.6Mn-0.4Zn-0.2Ce alloy as an example (based on mass percentage, it is composed of the following components: manganese: 0.6%, zinc: 0.4%, cerium: 0.2%, unavoidable impurities ≤ 0.05%, and the balance is magnesium), its preparation method includes the following steps:
[0018] (1) According to the alloy component ratio, pure magnesium is kept at 320° C. for 90 minutes under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide to sulfur hexafluoride is 95:5), and then the temperature is raised to 700° C. to melt the pure magnesium to obtain magnesium liquid, pure zinc, magnesium-manganese, and magnesium-cerium master alloys are selected as alloy materials, and the alloy materials are preheated at 225° C. for 75 minutes in turn, and then added to the magnesium melt in turn, and then the temperature is raised to 710° C. to melt the master alloy, and then the magnesium melt is stirred evenly and kept warm for 15 minutes, and then argon gas is blown into it for refining and slag removal to obtain a magnesium alloy melt, and then poured into a mold at 250° C. by gravity casting to obtain an alloy ingot;
[0019] (2) the alloy ingot obtained in step (1) is subjected to homogenization treatment and then immediately water-cooled, wherein the homogenization treatment is carried out by keeping the alloy ingot at 500° C. for 22 hours, and the quenching is carried out by water-cooling the alloy ingot at room temperature to room temperature; after keeping the alloy ingot at 350° C. for 90 minutes, the alloy is extruded at 350° C., wherein the extrusion ratio is 26:1 and the extrusion speed is 0.2 mm / s, and the alloy is air-cooled to room temperature to obtain the Mg-0.6Mn-0.4Zn-0.2Ce alloy;
[0020] The yield strength of the Mg-0.6Mn-0.4Zn-0.2Ce alloy obtained in step (2) is 280 MPa, and the elongation is 25%. After the alloy is immersed in a 3.5% NaCl solution for 15 days, the corrosion rate is 0.3 mm / Year.
[0021] Example 3
[0022] Taking Mg-0.6Mn-0.4Zn-0.2Ce-0.2Al alloy as an example (in terms of mass percentage, it is composed of the following components: manganese: 0.6%, zinc: 0.4%, cerium: 0.2%, aluminum: 0.2%, unavoidable impurities ≤ 0.05%, and the balance is magnesium), its preparation method includes the following steps:
[0023] (1) According to the alloy component ratio, pure magnesium is kept at 300° C. for 120 min under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide to sulfur hexafluoride is 90:10), and then the temperature is raised to 710° C. to melt the pure magnesium to obtain a magnesium melt, and pure zinc, pure aluminum, magnesium-manganese, and magnesium-cerium master alloys are selected as alloy materials, and the alloy materials are preheated at 250° C. for 60 min in sequence, and then added to the magnesium melt, and then the temperature is raised to 720° C. to melt the master alloy, and then stirred evenly and kept warm for 20 min, and then argon gas is blown into it for refining and slag removal to obtain a magnesium alloy melt, and then poured into a mold at 300° C. by gravity casting to obtain an alloy ingot;
[0024] (2) The alloy ingot obtained in step (1) is homogenized and then immediately quenched. The homogenization treatment is to keep the alloy ingot at 460°C for 26 hours. The quenching is to cool the alloy in water at room temperature to room temperature. After keeping the alloy in water at 320°C for 40 minutes, the alloy is extruded at 320°C. The extrusion ratio is 25:1 and the extrusion speed is 0.3 mm / s. After extrusion, the alloy is air-cooled to room temperature to obtain the Mg-0.6Mn-0.4Zn-0.2Ce-0.2Al alloy. The yield strength of the Mg-0.6Mn-0.4Zn-0.2Ce-0.2Al alloy obtained in step (2) is 275 MPa and the elongation is 30%. After the alloy is immersed in a 3.5% NaCl solution for 15 days, its corrosion rate is 0.28 mm / Year.
[0025] Comparative Example 1
[0026] The invention patent entitled "A preparation method for improving the plastic forming of rare earth magnesium alloy" (application publication number: CN112251657A) was published, in which the alloy obtained in Example 1 has the best performance. The preparation method of the obtained alloy includes: using a pit-type resistance furnace and a low-carbon steel metal mold to obtain a Mg-10Gd-1E-r 0.5Zr alloy metal ingot, and the raw materials used are pure magnesium, Mg-30Gd master alloy, Mg 30Er master alloy, Mg 24Zr master alloy, preheat the raw materials, heat the smelting furnace to about 450℃, put in pure magnesium and half of the magnesium-gadolinium alloy, add magnesium-erbium alloy and magnesium-X alloy at about 730℃, add magnesium-zirconium alloy and the remaining magnesium-gadolinium alloy after melting, stir the slag for 3min after melting, and then keep it warm for 15min, reach the melting temperature of about 730℃ for casting, cut and mill the ingot, and then keep it warm at 475℃ for 5h for solution treatment, hot extrude the alloy after solution treatment, the extrusion rate is 0.5mm / s, the extrusion temperature is 450℃, the extrusion ratio is 20, and the extruded plate is cross-rolled For rolling, the holding temperature of the first and second passes is 425°C, the holding time is 20 min, and the reduction of a single pass is 15%; the holding temperature of the third to fourth passes is 425°C, the holding time is 20 min, and the reduction of a single pass is 10%; the holding temperature of the fifth to eleventh passes is 425°C, the holding time is 10 min, and the reduction of a single pass is 10%; the holding temperature of the twelfth to nineteenth passes is 435°C, the holding time is 15 min, and the reduction of a single pass is 8%. The rolling rate is 8-10 m / min, the cumulative deformation is about 80%, the alloy yield strength is 249 MPa, and the elongation is 4.6%. The total alloy addition amount of the comparative example 1 is 11.5%, which is much higher than the alloy addition amount (<1.5%) of the present invention. Among them, the rare earth content of the comparative example 1 is 11%, which is much higher than the maximum rare earth content (≤0.2%) of the present invention. In addition, the present invention does not use the more expensive Gd, Er and Zr used in the comparative example 1, and the added elements of the two are completely different. In addition, the heat treatment (solution temperature is higher) and extrusion (extrusion temperature is higher) process parameters used in the present invention and the comparative example 1 are different, and the present invention omits the multi-pass cross rolling method used in the comparative example 1. Therefore, the process of the present invention is simple and saves production costs. When the alloy cost added in the comparative example 1 is much higher than that of the present invention, and the process used is more complicated than that of the present invention, the highest mechanical properties and plasticity of the alloy obtained in the comparative example 1 are lower than the lowest strength and plasticity of the alloy obtained in the present invention. In summary, compared with the comparative example 1, the present invention reduces the addition of alloy elements or rare earths, significantly reduces costs, simplifies the process flow, and obtains alloy mechanical strength and plasticity higher than the comparative example 1, respectively, and realizes the simultaneous improvement of the strength and plasticity of the magnesium alloy, and the comparative example 1 does not give the technical effect of the corrosion resistance of the present invention.
[0027] Comparative Example 2
[0028] The journal paper entitled "Improving the corrosion resistance of Mg-8Li-3Al-2Zn alloy bycombining Gd alloying and hot extrusion" (published in Journal of Alloys and Compounds, Journal Volume: Volume 964, Paper Published in June 2023, Paper Author Yuehua Sun et al.) mentioned in the experimental materials that the weight percentages of the selected materials are Li: 8.06%, Al: 2.97, Zn: 2.06%, Gd: 1.02, Zr: 0.2, and the balance is Mg. The alloy treatment process is: the homogenization treatment is: 300℃24h, the extrusion treatment: the extrusion temperature is 250℃, and the extrusion ratio is 23. The alloy element addition content of Comparative Example 2 (14.31%) is much higher than the alloy addition content of the present invention (<1.5%). The alloy disclosed in Comparative Example 2 was immersed in a 3.5% NaCl solution for 15 days, and the corrosion rate was 0.64 mm / Year, which was higher than the corrosion rate of the alloy obtained in the present invention, that is, the corrosion resistance was weaker than the alloy obtained in the present invention. Compared with Comparative Example 2, the present invention did not use Li, Gd and Zr disclosed in Comparative Example 2. The present invention used less element content and rare earth content, so the price was low and cost was saved. In addition, the process parameters used by the two were different. The minimum corrosion resistance of the alloy obtained by the present invention was better than the maximum corrosion resistance of the alloy obtained in Comparative Example 2.
[0029] Comparative Example 3
[0030] Take Mg-0.05Mn-0.22Al-0.04Ce-0.15Zn alloy as an example (calculated by mass percentage, it is composed of the following components: manganese: 0.05%, aluminum: 0.22%, cerium: 0.04%, zinc: 0.15%, unavoidable impurities ≤ 0.05%, and the balance is magnesium). The preparation method of the alloy comprises the following steps: (1) keeping pure magnesium at 290° C. for 40 minutes under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide to sulfur hexafluoride is 88:12) according to the proportion of alloy components, and then heating to 685° C. to melt the pure magnesium to obtain a magnesium melt; selecting pure aluminum, pure zinc, magnesium-manganese, and magnesium-cerium intermediate alloys as alloy materials, preheating the alloy materials at 275° C. for 45 minutes in turn, adding the alloy materials to the magnesium melt, and then heating to 690° C. to melt the intermediate alloy; stirring evenly and keeping the mixture warm for 25 minutes, and then blowing argon gas into the mixture for refining and slag removal to obtain a magnesium alloy melt; and then pouring the mixture into a mold at 180° C. by gravity casting to obtain an alloy ingot;
[0031] (2) The alloy ingot obtained in step (1) is homogenized and then immediately quenched. The homogenization treatment is to keep the alloy ingot at 440°C for 28 hours. The quenching is to cool the alloy in water at room temperature to room temperature. After keeping the alloy in water at 270°C for 50 minutes, the alloy is extruded at 270°C. The extrusion ratio is 16:1 and the extrusion speed is 0.4 mm / s. After extrusion, the alloy is air-cooled to room temperature to obtain a Mg-0.05Mn-0.22Al-0.04Ce-0.15Zn alloy. The yield strength of the Mg-0.05Mn-0.22Al-0.04Ce-0.15Zn alloy obtained in step (2) is 175 MPa and the elongation is 16%. After the alloy is immersed in a 3.5% NaCl solution for 15 days, the corrosion rate is 0.6 mm / year. Although Comparative Example 3 uses similar components and processes as the present invention, its component ratio and process parameters are not within the protection scope of the claims of the present invention, and its strength, plasticity and corrosion resistance are lower than the minimum mechanical properties and corrosion resistance of the alloy obtained by the present invention.
[0032] In summary, the present invention achieves the following excellent effects through the coordinated regulation of the interaction, ratio, process and process parameters among alloy components: Compared with the prior art, the present invention reduces the types of alloy additions, rare earth and content of added elements, while reducing the amount of alloy elements and rare earth additions, wherein the alloy addition amount is less than 1.5%, that is, a low-content and low-cost alloy, and simplifies the process, and the minimum strength, plasticity and corrosion resistance of the alloy obtained are better than the highest strength, plasticity and corrosion resistance obtained by the prior art, the yield strength of the alloy is ≥275MPa, and the elongation is ≥17.5%; after the alloy is immersed in a 3.5% NaCl solution for 15 days, the corrosion rate of the alloy is ≤0. 3mm / Year; The components, component ratios and process parameters of the embodiments of the present invention are different, but the performances are all different. Although Comparative Example 3 uses similar components and processes as the present invention, its component ratios and process parameters are not within the protection scope of the claims of the present invention. The various properties of the alloy obtained in Comparative Example 3 are lower than those of the alloy obtained in the present invention. This shows that the best performance of the alloy obtained in the present invention is not determined by a certain component, ratio or process parameter, but is achieved through the interaction, ratio, process and coordinated regulation of process parameters among the alloy components, and only within the protection scope of the claims of the present invention can the best performance of the alloy be achieved. The present invention significantly improves the microstructure of low-content magnesium alloys. Compared with the alloy microstructure disclosed in the prior art, the precipitated phase obtained by the present invention promotes dynamic recrystallization as a nucleation site, while the precipitated α phase and the segregation of elements at the grain boundaries can effectively pin grain boundaries and dislocations, promote the nucleation of dynamic recrystallization of deformed grains, hinder the abnormal growth of grains that have been dynamically recrystallized, and obtain finer dynamically recrystallized grains. At the same time, due to the grain boundary segregation of elements, the grain boundary mediated plasticity of the fine-grained magnesium alloy is suppressed, thereby greatly improving the yield strength and corrosion resistance of the magnesium alloy without reducing the plasticity of the alloy, and ultimately achieving the simultaneous improvement of the strength and plasticity and corrosion resistance of the magnesium alloy. The present invention is suitable for industrial production, improves production efficiency, simplifies production processes, reduces energy consumption and production costs, and solves the difficult problems of the difficulty in simultaneously improving the strength and plasticity and corrosion resistance of magnesium alloys and efficient industrial production.
Claims
1. A high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy, characterized in that: The high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy comprises the following components by mass percentage: composition: Manganese: 0.1-0.6%, zinc: 0.2-0.4%, cerium: 0.05-0.2% and aluminum ≤0.2%, alloy addition ≤1.4%, unavoidable impurities ≤0.05%, and the balance is magnesium. Its preparation method comprises the following steps: (1) According to the proportion of alloy components, under the protection of a mixed gas of carbon dioxide and sulfur hexafluoride, the volume ratio of carbon dioxide to sulfur hexafluoride is 90-99:1-10, pure magnesium is kept at 300-350° C. for 60-120 min, and then the temperature is raised to 690-710° C. to melt the pure magnesium to obtain a magnesium melt, pure zinc, pure aluminum, magnesium-manganese, and magnesium-cerium master alloys are selected as alloy materials, the alloy materials are preheated at 200-250° C. for 60-90 min, and then added to the magnesium melt in sequence, and then the temperature is raised to 700-720° C. to melt the master alloy, and then stirred evenly and kept warm for 10-20 min, and then argon gas is blown into it for refining and slag removal to obtain a magnesium alloy melt, and then poured into a mold at 200-300° C. by gravity casting to obtain an alloy ingot; (2) homogenizing and quenching the alloy ingot obtained in step (1), then extruding it at 300-350° C. for 60-120 min, and air-cooling it to room temperature to obtain a high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy, wherein the homogenizing treatment is carried out at 460-500° C. for 22-26 h; the quenching is carried out at room temperature and water-cooled to room temperature; the extrusion is carried out at an extrusion ratio of 25-28:1 and an extrusion speed of 0.1-0.3 mm / s; The high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy obtained in step (2) has a yield strength of ≥275 MPa and an elongation of ≥17.5%; after being immersed in a 3.5% NaCl solution for 15 days, the corrosion rate of the alloy is ≤0.3 mm / Year.
2. A high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy according to claim 1, characterized in that: According to mass percentage, the manganese is 0.2-0.5%, the zinc is 0.25-0.35%, the cerium is 0.1-0.15%, and the aluminum is 0≤≤0.15%.
3. The high-strength, plastic, corrosion-resistant, micro-alloyed, low-cost magnesium alloy according to claim 1, characterized in that: The magnesium alloy obtained in step (2) has a yield strength of 280-320 MPa and an elongation of 25-30%.
